Determining the Competitiveness of Türkiye’s Selected Defense Products: A Revealed Comparative Advantage and Comparative Export Performance - Zehra Vildan Serin; Seda Yeldan (İktisat Politikası Araştırmaları Dergisi)
Türkiye has had strategic importance for the defense industry throughout history due to its geopolitical status. Türkiye has taken important steps in the defense industry in recent years by reducing its dependence on foreign sources and has come to a competitive position with many countries. Türkiye has succeeded in increasing its domestic production in the defense industry, especially since 2000. The main purpose of this study is to determine Türkiye’s competitiveness regarding armored vehicle, artillery, missile, and ship product groups with the USA, Russia, China, France, and Germany as the global powers in defense industry exports. The study aims to reveal whether Türkiye has an advantageous position regarding its competitiveness with the selected countries in the world defense industry market. This research will also contribute to the literature, which contains a limited number of studies on the subject. This study applies the revealed comparative advantages (RCA) and comparative export performance (CEP) index methods to the 2010-2020 period. The research findings show Türkiye’s to have high competitive power in terms of armored vehicle exports over the 2010-2020 period according to the RCA index values. Türkiye surpassed Russia in terms of artillery product requirements and CEP index values in 2015. Although the index follows a fluctuating course, the product export performance from non-commissioned officers when selected between 2011-2017 is high. The comparative export performances of the missile CEP index values are generally unsatisfactory. Türkiye shows a flawed performance regarding missile exports. In2010 and 2019, the export performance for ships was determined to be better than Russia. Export performance with the USA was high after 2012. The continuation of Türkiye’s competitive advantage against the USA, Russia, China, France, and Germany regarding the export of defense armored vehicles, artillery, and ship products will depend on Türkiye increasing the importance it gives to research and its orientations toward these product groups and on maintaining its strategic trade policies.